2018
DOI: 10.1002/jper.17-0381
|View full text |Cite
|
Sign up to set email alerts
|

Oral flurbiprofen spray for mucosal graft harvesting at the palatal area: A randomized placebo‐controlled study

Abstract: Oral flurbiprofen spray reduces patient's morbidity, however it might have negative effects on epithelialization of secondary wound healing after FGG operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
1
19
1
Order By: Relevance
“…Limited donor tissue in the cases where inadequate amount of palatal tissue thickness and/or a bigger dimension of CTG is needed, as in the treatment of MAGRs, is claimed to be among those disadvantages (Zucchelli et al., 2010). Moreover, subepithelial CTG (SCTG), either harvested by “trap‐door” (TD) (Bruno, 1994; Harris, 1997) or “single‐incision” (SI) approaches (Hurzeler & Weng, 1999; Lorenzana & Allen, 2000), has been frequently associated with postoperative pain and discomfort, as well as palatal flap necrosis/dehiscence at the donor site (Del Pizzo et al., 2002; Griffin et al., 2006; Wessel & Tatakis, 2008; Zucchelli et al., 2010; Gobbato et al., 2016; Isler et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Limited donor tissue in the cases where inadequate amount of palatal tissue thickness and/or a bigger dimension of CTG is needed, as in the treatment of MAGRs, is claimed to be among those disadvantages (Zucchelli et al., 2010). Moreover, subepithelial CTG (SCTG), either harvested by “trap‐door” (TD) (Bruno, 1994; Harris, 1997) or “single‐incision” (SI) approaches (Hurzeler & Weng, 1999; Lorenzana & Allen, 2000), has been frequently associated with postoperative pain and discomfort, as well as palatal flap necrosis/dehiscence at the donor site (Del Pizzo et al., 2002; Griffin et al., 2006; Wessel & Tatakis, 2008; Zucchelli et al., 2010; Gobbato et al., 2016; Isler et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There were additional studies ( n = 3) retrieved from the electronic search which reported haemorrhagic events with flurbiprofen (in formulations synonymous with oromucosal spray/lozenge) but at a low dose other than 8.75 mg ( Türk et al, 2018 ; Isler et al, 2018 ; Dionne et al, 2004 ). These did not fulfil the eligibility criteria for the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Where additional haemorrhagic events were identified with low doses of flurbiprofen, these were observed in patients undergoing oral surgery (e.g., tonsillectomy, palatal graft harvesting surgery, mandibular extraction) ( Türk et al, 2018 ; Isler et al, 2018 ; Dionne et al, 2004 ). Bleeding events were described as post-operative haemorrhage or delayed bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Mucogingival tissue deformities are a group of conditions characterised by inadequate thickness of keratinised gingival tissue, which could result in gingival recession, unsatisfactory aesthetics, and poor chewing function [31][32][33][34][35]. Previous studies have demonstrated that an autogenous palatal mucosal graft was the most predictable grafting material to facilitate keratinised gingival repair [36]. However, this approach could lead to secondary damage in the donor site and other drawbacks.…”
Section: Discussionmentioning
confidence: 99%